THE FUNCTION OF THE SALE AND PURCHASE DEED IN THE TRANSFER OF LAND OWNERSHIP RIGHTS - Akbar Rahmat Irhamulloh Abba; Dimas Al Hakim; I Putu Aris Udiana Putra (Journal Equity of Law and Governance, 2021)
Land is one of the wealth guaranteed by the State of Indonesia for the prosperity of its people. The Country of Indonesia is a legal state in accordance with article 1 paragraph 3 of the Constitution of the Republic of Indonesia in 1945 which indicates that all actions taken by the authorities and the public must be based on the applicable law. Likewise in the field of land, that all actions taken by both the ruler and the public must always be based on the prevailing law which is the provisions of the prevailing laws and regulations. The purpose of this research is to analyze the legal requirements of the transfer of property rights to land and to know the function of the deed of sale and sale in its relationship in the transfer of property rights to land. This type of research is normative juridical research. The problem approach used to examine this issue is the approach of legislation. Legal materials used are primary legal materials and secondary legal materials. The method of analysis of legal materials is to use the technique of inventorying and classifying legal materials and to answer the problem of this research using the principle of preference where to point to the law which takes precedence. The results of the discussion show that for the valid terms of sale and purchase of property on land must meet the provisions in the Civil Law and Agrarian Principal Law which is further regulated in Government Regulation No. 24 of 1997 on Land Registration. The legal consequence of the transfer of property rights to land according to the Basic Agrarian Law is that the authority of the old land owner is automatically lost and transferred to the buyer, due to the dualism of regulations regarding the sale and purchase of land rights, namely in accordance with the provisions of the Civil Code and according to the provisions of the Law In the Basic Agrarian Law, the principle of preference is used here, namely more specific provisions overriding more general provisions. So the provisions in the Basic Agrarian Law override the provisions of the Civil Code regarding the sale and purchase of land rights.